English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-17 13:28:11 · 3 answers · asked by Rave N 1 in Science & Mathematics Mathematics

3 answers

f(u) = 2*u^(1/2) + 3*u^(1/2)
===>
df(u)/dx = d(2*u^(1/2))/dx + d(3*u^(1/2))/dx

df(u)/dx = 2d(u^(1/2))/dx + 3d(u^(1/2))/dx

df(u)/dx = (2 + 3) d(u^(1/2))/dx
df(u)/dx = 5*(1/2) (u^(1/2-1)

df(u)/dx = 5/2*u^(-1/2)

2007-06-17 13:47:25 · answer #1 · answered by CHARTIGER 2 · 0 0

2u^(1/2) + 3u^(1/2) = 5u^(1/2)

derivative is

(5/2)u^(-1/2)

simplified to

(5sqrt u) / 2u

2007-06-17 20:54:45 · answer #2 · answered by jimbob 6 · 0 0

2*u^(1/2)+3*u^(1/2)
= 5u^(1/2)
f'(u) = 2.5 /u^1/2

2007-06-17 20:42:44 · answer #3 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers